Species of Centaurium Hill. in Iraq and its geographical distribution - Baghdad Science Journal (مجلة بغداد للعلوم, 2013)
Comparative taxonomic study has been compeleted for the species of the. genus Centaurium Hill. of Iraq. So the morphological characters were studied comparatively for the first time form Iraqi materials. Stems, leaves ,infloresences and reproductive organs characters were a good taxonomic importance. Geographical distrtribution has been done for the species of the genus in addition to the environment information. The results were presented with schedules, tables, maps and micrographs. Taxonomic key for the species separation was also presented.